Understanding and preventing police deviance and corruption based on experiences and trends in the United States - Albrecht, James F. (Critical issues and global perspectives ; volume 1: Special topics in policing, 2024)
Police deviance can generally be defined as disregarding agency policy, rules and regulations, societal expectations, and/or criminal law. From a more practical perspective, five basic types of police deviance can be specified: (1) corruption, (2) criminality, (3) excessive use of force, (4) abuse of authority, and (5) misconduct. A comprehensive analysis of the experiences of numerous large metropolitan police departments in the United States since the 1960s will be undertaken in an effort to better understand the underlying theoretical and causal factors that contribute to these undesirable and unacceptable phenomena. This evaluation will guide the formulation of practical policy recommendations that should be considered and implemented to deter corruption, criminal behavior, and serious abuses and to enhance leadership and professional standards within law enforcement organizations.